Dose-related antinociceptive effects of intravenous buprenorphine in cats - Steagall, Paulo V. M. [UNESP]; Mantovani, Fernanda B. [UNESP]; Taylor, Polly M.; Dixon, Mike J.; Luna, Stélio Pacca Loureiro [UNESP] (Elsevier B.V., 2009)
The dose-related antinociceptive effects of intravenous (IV) buprenorphine were evaluated in cats. Thermal (TT) and mechanical threshold (MT) devices were used for nociceptive stimulation. After baseline threshold recordings, buprenorphine was administered IV (0.01, 0.02 or 0.04 mg/kg; B1, B2 and B4, respectively) in a randomised, blinded and cross-over study. Data were analysed by ANOVA (P < 0.05) using 95% confidence intervals (CI). TT increased 15, 30, 45 min and 1 (5.2 +/- 2.7 degrees C), 2, 3 and 4 h after B 1; 15, 30, 45 min and 1 (5.1 +/- 3.9 degrees C) and 2 h after B2, and 15, 30, 45 min and 1 (5.4 +/- 3.3 degrees C), 2, 3, 6 and 8 h after B4. MT increased 15 and 45 min after 132 (260 171 mmHg), and 30 (209 116 mmHg) and 45 min and I and 2 It after B4. At 45 min, MT values were significantly higher after B2 compared to B I (P < 0.05). With MT, B2 and B4 produced more antinociception and longer duration of action than B1, respectively. No dose response to thermal stimulation was detected. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Buprenorphine; Dose-response; Cat; Antinociception; Threshold